Evaluating Outcomes Related to Donor and Recipient Metabolic Environment: Macrosteatotic Allografts and Nonalcoholic Steatohepatitis. Issue 4 (5th November 2021) - Altshuler, Peter J.; Dang, Hien; Frank, Adam M.; Shah, Ashesh P.; Glorioso, Jaime; Zhan, Tingting; Rios Diaz, Arturo; Shaheen, Osama; Ramirez, Carlo B.; Maley, Warren R.; Bodzin, Adam S.
Abstract : The increasing prevalence of nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) affects both recipient and donor populations in liver transplantation. Presently, it is unclear whether transplantation of macrosteatotic allografts is affected by the metabolic milieu of liver transplant recipients. This study investigates fatty liver disease at the intersection of donor and recipient. A retrospective review of the Organ Procurement and Transplantation database identified 5167 NASH and 26, 289 non‐NASH transplant recipients who received transplants from January 1, 2004, to June 12, 2020. A total of 12, 569 donors had allografts with no macrosteatosis (<5%), 16, 140 had mild macrosteatosis (5%‐29%), and 2747 had moderate to severe macrosteatosis (≥30%). Comparing recipients with NASH to propensity score–matched (PSM) recipients without NASH demonstrated noninferior graft and patient survival up to 10 years in patients with NASH. Similar trends were observed in subgroup analyses of transplants within each strata of allograft macrosteatosis. Assessing allograft macrosteatosis specifically in the NASH population demonstrated that allografts with ≥30% macrosteatosis were associated with reduced early graft survival (30 days, 93.32% versus 96.54% [ P = 0.02]; 1 year, 84.53% versus 88.99% [ P = 0.05]) compared with PSM grafts with <30% macrosteatosis. Long‐term graft survival at 5 and 10 years, however, was similar. The use of carefully selected macrosteatotic allografts can be successful in both recipients with NASH and recipients without NASH. The metabolic environment of patients with NASH does not appear to adversely affect outcomes with regard to the allograft when controlled for numerous confounders. It is, however, important to remain cognizant of the potential for high‐risk macrosteatotic allografts to negatively affect outcomes.